PERAN HAKIM DALAM PENEGAKAN HUKUM LINGKUNGAN HIDUP (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2022)
As one of the institutions of state power, the court institution has a juridical duty in carrying out the duties of the state, so that the pillars of the state become upright and serve to protect all citizens. One of the pillars of the state is the establishment of justice as a form of sovereignty and authority of the state in the eyes of the international community and for the People of Indonesia as stakeholders or stakeholders in the establishment of Indonesian state law. The juridical task of the court that must be carried out in the holding of the power of the state in the judicial field is to uphold justice on the basis of legal truth. The practice of applying the law by the court must be accountable to the community, so that the court's decision is required to be in accordance with common sense. Institutionally, the decision of the first level court must be able to be accounted for if one of the parties makes a legal effort to the appeals court. Similarly, the appeal rate decision must be accounted for if one of the parties makes a cassation effort to the Supreme Court. The formulation of the issue raised is how the role of judges in environmental law enforcement. Research uses normative juridical juridical. The result found is that judges have a role in the enforcement of environmental law that realizes its protective function for environmental protection and the human right to obtain and use the surrounding natural environment. And the enforcement of sanctions for violators of environmental law must be able to have a special prevensi effect and general prevensi. Keywords: Judge, law enforcement, environment